MARS/NDRI/KSU Communications Workshop: Part 6. Summary of Responses to Day 2 Nominal Group Discussion Questions - Leslie, John F. (My University, 2022)
A. Identify Communication Strategies for Important Mycotoxin Issues of Relevance to Consumers – Pages 1-4 B. Identify Communication Strategies for Important Mycotoxin Issues of Relevance to Producers, Traders & Distributors – Pages 5-12 C. Identify Communication Strategies for Important Mycotoxin Issues of Relevance to Health Professionals – Pages 13-15 D. Identify Communication Strategies for Important Mycotoxin Issues of Relevance to Policy Makers & Regulators – Pages 16-21
Keywords: Aflatoxin; Food Safety; Mycotoxins; Nepal; Public Health; Risk Communication